Efficacy of Aharaj Rajaswalacharya on Kashtartava wsr to Primary dysmenorrhea: A Pilot Study - Beravat, Bhumika; Jadhav, Shriniwas; Bagul, Aparna (Journal of Neonatal Surgery, 2024)
Introduction: Dysmenorrhea, characterized by painful menstrual cramps, significantly impacts the quality of life for many women. It is broadly classified into two types — primary dysmenorrhea (also called spasmodic dysmenorrhea), which occurs without underlying pelvic pathology, and secondary or congestive dysmenorrhea, which arises due to identifiable causes such as endometriosis or pelvic inflammatory disease. The clinical presentation of Kashtārtava closely parallels that of primary dysmenorrhea, as both are characterized by painful uterine contractions during menstruation without structural abnormalities. Ayurvedic texts attribute this condition mainly to Vāta vitiation (particularly Apāna Vāta), leading to spasmodic pain in the lower abdomen and pelvic region. Methods: A cohort of 10 women aged 14-30 years with primary dysmenorrhea was selected for this study. Participants were instructed to follow dietary modifications (Havishyanna i.e., Shali, ilk, Yava, Ghrita 30 gm TDS, as per Ayurvedic classics during their menstrual phase for three consecutive cycles. Dietary modifications included intake of warm, easily digestible foods, and avoidance of cold and heavy foods. Pain intensity was measured using a Visual Analog Scale (VAS) and WaLIDD score before and after the intervention. Results: Data analysis showed a marked reduction in the intensity of menstrual pain among participants. The mean VAS score decreased from 6.8 (pre-intervention) to 2.3 (post-intervention) (p < 0.01). The mean WaLIDD score decreased from 6.5 (pre-intervention) to 1.6 (post- intervention) (p < 0.01). Additionally, participants reported relief in other menstrual symptoms, such as bloating and fatigue. Conclusion: Dietary modifications as per Ayurvedic classics show promise in managing Primary dysmenorrhea, providing a natural and holistic approach to alleviate menstrual pain and associated symptoms. This pilot study lays the groundwork for future research to explore and traditional dietary practices..